Exploring Effective Written Feedback Strategies in Business Writing Education: Teachers’ Approaches and Students’ Views - Listiana, Tri Ananti; Ali, Helena Verusha; Sari, Farnia; Wahyudi, Agus (Universitas Hamzanwadi, 2023)
The importance of business correspondence mastery for students in business schools is critical, as it differs significantly from academic writing in humanities programs. Its primary aim is to prepare students for professional success and service excellence in their future careers. This study explores the subtleties of written corrective feedback in business writing courses. It examines the types and techniques used by lecturers and analyzes students' perceptions of this feedback. Employing a mixed-methods research design, the study combines observational and qualitative data through document analysis, questionnaires, and semi-structured interviews. It involves lecturers and 65 students from a business writing course, with a specific focus on analyzing 64 student assignments for lecturers' feedback practices. The results indicate a preference for indirect feedback, primarily addressing grammatical errors through techniques like circling, underlining, and highlighting, complemented by direct comments and questions. Most students viewed this feedback positively, noting its benefit in improving grammatical skills, though some preferred more direct feedback on content and structure. These findings underscore the need for diverse feedback methods in business writing education to accommodate varied student needs and enhance engagement and learning outcomes. The study emphasizes the significance of customized feedback strategies in the effectiveness of teaching and learning in business writing courses.Top of Form